2013
DOI: 10.1002/arch.21087
|View full text |Cite
|
Sign up to set email alerts
|

MOLECULAR CHARACTERIZATION OF TWO CARBOXYLESTERASE GENES OF THE CITRUS RED MITE, Panonychus citri (ACARI: TETRANYCHIDAE)

Abstract: The citrus red mite, Panonychus citri, is known for its ability to rapidly evolve resistance to insecticides/acaricides and to adapt to hosts that produce toxins. To get better insight into the detoxification mechanism of P. citri, two carboxylesterase (CarE) genes, PCE1 and PCE2, were isolated and characterized. PCE1 and PCE2 contained open reading frames of 1,653 and 1,392 nucleotides, encoding proteins of 550 and 463 amino acid residues, respectively. Phylogenetic analyses showed that PCE1 and PCE2 were mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Besides PcE1 , isolated from our previously reported transcriptome [27], two novel CarE genes ( PcE7 and PcE9 ) were cloned, respectively. No point mutation occurred among different field strains of P. citri .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides PcE1 , isolated from our previously reported transcriptome [27], two novel CarE genes ( PcE7 and PcE9 ) were cloned, respectively. No point mutation occurred among different field strains of P. citri .…”
Section: Resultsmentioning
confidence: 99%
“…The current bioassay found the synergist TPP dramatically increased the toxicity of fenpropathrin, indicating that CarEs-mediated detoxification was probably an important mechanism of pyrethroid resistance in P. citri . In the current study, besides PcE1 that was identified to participate in the detoxification of acaricides [27], two novel CarE genes ( PcE7 and PcE9 ) were chosen from transcriptome data as the candidate genes based on the qPCR results of their over-expression in fenpropathrin-resistant filed strains of P. citri . The subsequent phylogenetic analysis with CarE genes from T .…”
Section: Discussionmentioning
confidence: 99%
“…The citrus red mite, Panonychus citri (McGregor), has a worldwide distribution and is an economically important citrus pest that rapidly adapts to hosts and has evolved resistance to acaricides [2629]. Although biological control has been successful in mite management, chemical control is still the main strategy against this pest in the field.…”
Section: Introductionmentioning
confidence: 99%
“…There have been some recent studies on detoxification enzymes that might be involved in development of resistance in P. citri , such as two cytochrome P450 genes, CYP4CF1 and CYP4CL2 [22]. Similarly, the results of acaricide challenge experiments showed that CarE genes, PCE1 and PCE2 , may participate in the detoxification of avermectin and pyridaben [23]. By comparing the correlation coefficient of susceptibility of citrus red mite to pyridaben in nine field populations, along with their GST activities, it was suggested that GSTs could possibly be involved in detoxification of pyridaben in several field populations [24].…”
Section: Introductionmentioning
confidence: 99%